Unleashing the Power of AI: Revolutionising Indian Classrooms with AI-Driven Pedagogical Breakthroughs - K, Kavitha; Joshith, V. P (Indian Journal of Educational Technology, 2025)
Artificial intelligence (AI) is revolutionising education by enhancing accessibility, customisation, and engagement. AI applications, such as virtual tutoring, automation, and adaptive learning, are gaining ground in various domains of education. Forecasts about AI’s journey in education indicate that nearly all educational sectors, from school education to various technical, professional, and non-technical higher education fields, will progressively rely more on AI technologies and tools. The growth of AI technology over time and how it can be utilised in the education sector, ranging from cutting-edge methods of instruction to effective instructional strategies and universal access to education, are addressed briefly in this article. Further, it explores AI’s many potential application-related impacts on Indian education. It has been suggested that challenges such as socio-religious taboos, knowledge gaps, digital divide, shortage of specialists, and inadequate training initiatives must be addressed to incorporate AI technologies ethically in Indian education effectively.